CORE NURSING SKILLS: PROCEDURE MANUAL 2ND EDITION 2020 - Mohd Zain, Dr Norhasmah; Samsudin, Norazliah (2020)
This book contains a core procedure manual for nursing skills. The purpose of this book is to coordinate the teaching and learning process of nursing skills.This book describes the steps in implementing each procedure systematically and rationally to give an understanding of the importance of the steps being taken. Additionally, the book also emphasizes aspects of communication with patients, respecting patients as an individual providing patients with privacy and safety during the procedure.I would like to thank all the authors who have contributed and reviewed the writing of their respective procedures. I would also like to thank all the editors who have worked hard with me in producing this book. Hence, I would also like to thank the Chairman of the Nursing Program for trusting me and the editors to produce this book for the nursing program.Finally, I and my editors are hoping that this book will benefit all students and lecturers who will use this book. Specifically, I hope this book will inspire a more skilled generation of learners about performing nursing procedures.